The Oxford Guide to the Book of Common Prayer : a Worldwide Survey - Hefling, Charles, 1949-; Shattuck, Cynthia L., 1947- (Oxford University Press, 2006)
The Book of Common Prayer runs like a golden thread through the history of the Church of England and the worldwide Anglican Communion. The Oxford Guide to the Book of Common Prayer is the first comprehensive guide to the history and usage of the original Book of Common Prayer and its numerous descendants throughout the world. It shows how a seminal text for Christian worship and devotion has inspired a varied family of religious resources that have had an influence far beyond their use in the churches of a single tradition. The Guide is unique. In it, experts from every part of the globe and e.